Analysis of Lead (Plumbum) Metal Levels in the Urine of Motorcycle Mechanics in Medan Helvetia District, Medan City - Ziza Fahriza; Dyna Grace Romatua Aruan (Laboratory Journal of Infectious Diseases, 2025)
Lead (Pb) is one of the pollutants originating from vehicle exhaust emissions and materials from vehicle components, such as gasoline, oil, and used batteries. Workshop workers are among the occupations that are highly vulnerable to lead exposure, as their daily activities involve continuous exposure to vehicle exhaust fumes and direct contact with materials from vehicle components during work, thereby increasing the risk of lead exposure. Sampling was conducted at motorcycle workshops located on Jalan Gaperta in Medan City, North Sumatra, and the measurement of lead levels in urine was carried out at the Regional Health Laboratory in Medan City. The purpose of this study was to analyze lead (Pb) levels in the urine of motorcycle workshop workers on Jalan Gaperta, Medan, North Sumatra. The method used in this study was Atomic Absorption Spectrophotometry (AAS). The samples consisted of urine from ten motorcycle workshop workers. The results showed that the highest lead level was found in sample Z04, at 52,5 µg/dL, while the lowest lead level was found in sample Z02, at 3,5 µg/dL. These results indicate that the lead levels in some motorcycle workshop workers exceeded the threshold limit established in the Regulation of the Minister of Health of the Republic of Indonesia No. 1406/MENKES/SK/IX/2002, which states that the permissible threshold limit for lead levels in urine specimens is 10–25 µg/dL.